Improving Climate-Change Literacy and Science Communication Through Smart Device Apps - Leuzinger, Sebastian; Borrelle, Stephanie B.; Jarvis, Rebecca M. (Frontiers in Education, 2019)
Global change clearly one of the most important issues of the 21st century. Understanding of the impacts of large-scale human activities on communities, and how the natural world is being affected is arguably the largest area of research outside of the health sciences, and the two are intricately linked. Yet despite scientific consensus on human-induced climate change, many publics remain divided about its existence and impacts. More alarming still are the contradictory positions from leading governments around the world to address climate change. The most convincing scientific evidence is in vain if scientists fail to communicate key facts to policy makers or to the general public. Here, we investigate various ‘snakes’ (pitfalls) and ‘ladders’ (emerging opportunities) in science communication. Using the example of the ‘Global Change App’, we argue that science education apps may be a promising and underrated way forward to improve how information is communicated between scientists, students and citizens. Smart device apps could be an effective way translate research outputs beyond scientific journals, support science teaching, and make information on global change more translatable and relevant to the general public.